A Polarimetric SAR and Multispectral Remote Sensing Approach for Mapping Salt Diapirs: Axel Heiberg Island, NU, Canada. Issue 1 (2nd January 2019) - Harrington, Elise M.; Shaposhnikova, Maria; Neish, Catherine D.; Tornabene, Livio L.; Osinski, Gordon R.; Choe, Byung-Hun; Zanetti, Michael
Abstract: Remote sensing has revolutionized resource exploration by enabling quick surveillance of large areas. Quad-polarimetric synthetic aperture radar (SAR) is useful for assessing surface roughness, but few studies have applied it for geological mapping. Located in the Canadian Arctic, Axel Heiberg Island is a suitable site for exploring remote predictive geologic mapping techniques that combine quad-polarimetric SAR and multispectral datasets. The island has extensive rock exposure, with little interference from vegetation and snow in late summer. Axel Heiberg Island has the second highest concentration of salt diapirs globally. As a result, it also hosts extensive secondary salt deposits that have been weathered and precipitated away from their source. Because diapirs frequently provide structural traps for petroleum reservoirs, it is important to distinguish between diapiric and non-diapiric salt during early exploration. This study maps diapirs and secondary salts using multispectral data and characterizes them in polarimetric SAR. Diapirs appear rough in C-Band and L-Band radar, whereas the secondary salts appear smooth at both (cm–dm) scales. Field observations confirm salt diapirs are rough at the millimeter–meter scales, whereas secondary salts precipitate on smoother surfaces. These results show that radar can help differentiate between diapiric and secondary salt exposures, which will assist in future resource exploration.